Dynamic characteristics of nanocomposite on the basis of porous Al2O3 doped by liquid crystal with magnetite under carbon monoxide influence - Vistak, Maria; Prystay, Taras; Petryshak, Vasyl; Sushynskyi, Orest; Mikityuk, Zinoviy (Photonics Letters of Poland, 2016)
In this paper dynamics characteristics of nanocomposite on the basis of cholesteric liquid crystal (CLC) with magnetite dopant introduced into porous structures are studied. We studied the behavior of spectral characteristics of transmittance of CLC2103L with Fe3O4 introduced in porous structures of Al2O3 under carbon monoxide influence. The diameter pores of Al2O3 is 20 nm, 35 nm and 50 nm, and CO concentration is in the range of 0-100 mg/m3. Interaction of investigated nanocomposite is the most intensive in the first minutes of CO influence. Further increase of interaction time does not lead to changes in the structure of the CLC. Full Text: PDF References S. Youssef, J. Podlecki, R. Habchi, M. Brouche, A. Foucarana, D. Bouvier, N. Brillouet, P. Coudray, "Innovative prototype of a zinc-oxide based optical gas sensor", Sens. and Act. B. 173, 391 (2012). CrossRef N.Yamazoe, G. Sakai, K. Shimanoe, "Oxide Semiconductor Gas Sensors", Catalysis Surveys from Asia 7, 63 (2003). CrossRef B. W. Kooa, C. K. Songa, C. Kimb, "CO gas sensor based on a conducting dendrimer", Sens. and Act. B 77. 432 (2001). CrossRef O. Sushynskyi, M. Vistak, Z. Gotra, A. Fechan, Z. Mikityuk, "Silicon dioxide nanoporous structure with liquid crystal for optical sensors", Proc. SPIE 9127, 91271F (2014). CrossRef A. Andrushchak, Z. Hotra, Z. Mykytyuk, M. Vistak, T. Prystay, O. Sushynskyi, "Nanostructures on the Basis of Porous Alumina with Intercalated with Cholesteric Liquid Crystal", Mol. Cryst. and Liq. Cryst. 611, 132 (2015). CrossRef O. Aksimentyeva, Z. Mykytyuk, A. Fechan, B.Tsizh, O. Sushynskyi, "Cholesteric Liquid Crystal Doped by Nanosize Magnetite as an Active Medium of Optical Gas Sensor", Mol. Cryst. and Liq. Cryst. 589, 83 (2014). CrossRef M. Vistak, O. Sushynsky, Z. Mykytyuk, O. Aksimentyeva, Y. Semenova, "Sensing of carbon monoxide with porous Al2O3 intercalated with Fe3O4 nanoparticles-doped liquid crystal", Sens. and Act. A: Physical. 235, 165 (2015). CrossRef